2014
DOI: 10.1007/s40262-014-0166-x
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam Pharmacokinetics in Morbidly Obese Patients Following Semi-Simultaneous Oral and Intravenous Administration: A Comparison with Healthy Volunteers

Abstract: BackgroundWhile in vitro and animal studies have shown reduced cytochrome P450 (CYP) 3A activity due to obesity, clinical studies in (morbidly) obese patients are scarce. As CYP3A activity may influence both clearance and oral bioavailability in a distinct manner, in this study the pharmacokinetics of the CYP3A substrate midazolam were evaluated after semi-simultaneous oral and intravenous administration in morbidly obese patients, and compared with healthy volunteers.MethodsTwenty morbidly obese patients [mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
92
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(114 citation statements)
references
References 47 publications
14
92
3
2
Order By: Relevance
“…The significant difference in oral bioavailability reported in this study (87) may result from the larger body weights of the subjects compared to the previous study by Greenblatt et al (81), who reported no difference in bioavailability (mean body weight of 144 kg versus 117 kg). The observed higher bioavailability could be explained by an increased splanchnic blood flow (19), which may lead to reduced contact between midazolam and intracellular CYP3A enzymes in the gut wall.…”
Section: The Influence Of Obesity On Oral Bioavailability and Absorptcontrasting
confidence: 82%
See 2 more Smart Citations
“…The significant difference in oral bioavailability reported in this study (87) may result from the larger body weights of the subjects compared to the previous study by Greenblatt et al (81), who reported no difference in bioavailability (mean body weight of 144 kg versus 117 kg). The observed higher bioavailability could be explained by an increased splanchnic blood flow (19), which may lead to reduced contact between midazolam and intracellular CYP3A enzymes in the gut wall.…”
Section: The Influence Of Obesity On Oral Bioavailability and Absorptcontrasting
confidence: 82%
“…This study design allowed for the characterization of both clearance and bioavailability in a single pharmacokinetic study. Results of this study show an increased bioavailability (60 ± 13% versus 28 ± 7%, P < 0.01) and a lower oral absorption rate (0.057 ± 14% min −1 versus 0.13 ± 5 min −1 , P < 0.01), but no influence of obesity on systemic clearance in morbidly obese patients compared to healthy volunteers (87). Dose simulations of the final population pharmacokinetic model showed that after a 7.5-mg oral midazolam, C max is only slightly lower, whereas T max is increased for morbidly obese patients (Figure 2c).…”
Section: The Influence Of Obesity On Oral Bioavailability and Absorptmentioning
confidence: 61%
See 1 more Smart Citation
“…Ulvestad et al ont d'ailleurs décrit une diminution du contenu hépa-tique et intestinal en CYP3A4 avec l'IMC [22]. En revanche, dans une étude récente, Brill et al ont évalué la pharmacocinétique du midazolam administré par voie orale et par voie intraveineuse chez des sujets obèses et des sujets non obèses [23]. Ils ont montré que la biodisponibilité du midazolam était supérieure chez les sujets obèses, tandis que la clairance n'était pas modifiée (après administration orale ou intraveineuse), ces données allant dans le sens d'une diminution de l'effet de premier passage, voire d'une augmentation de la perméabilité intestinale chez les patients obèses.…”
Section: Enzymes Transporteurs Et Obésitéunclassified
“…The authors attributed a higher midazolam clearance in the obese adolescents group to higher cytochrome P450 3A enzyme activity when compared to the morbidly obese adults group. However, the surgery type in the obese adults appears to have been exclusively laparoscopic procedures, whereas the surgery in the obese adolescents appears to have been predominantly orthopaedic and otolaryngeal procedures [2,3]. Laparoscopy, with the associated pneumoperitoneum, has been shown to decrease portal venous blood flow by approximately half, with a paradoxical increase in hepatic artery blood flow by approximately 20%, and apparent effects on drug clearance [4].…”
mentioning
confidence: 99%